Encephalitic Arboviruses of Africa: Emergence, Clinical Presentation and Neuropathogenesis - Klein, Robyn S. (Frontiers in Immunology, 2021)
Many mosquito-borne viruses (arboviruses) are endemic in Africa, contributing to systemic and neurological infections in various geographical locations on the continent. While most arboviral infections do not lead to neuroinvasive diseases of the central nervous system, neurologic diseases caused by arboviruses include flaccid paralysis, meningitis, encephalitis, myelitis, encephalomyelitis, neuritis, and post-infectious autoimmune or memory disorders. Here we review endemic members of the Flaviviridae and Togaviridae families that cause neurologic infections, their neuropathogenesis and host neuroimmunological responses in Africa. We also discuss the potential for neuroimmune responses to aide in the development of new diagnostics and therapeutics, and current knowledge gaps to be addressed by arbovirus research.